Taxonomy and distribution of the green algal genus Halimeda (Bryopsidales, Chlorophyta) in Brazil - Bandeira-Pedrosa,Maria Elizabeth (2004)
Halimeda is a genus of calcified coenocytic green algae with a well known ecological importance in some tropical areas. Bleached calcified segments of Halimeda may accumulate in large deposits of economic potential as is the case in the northeastern coast of Brazil. In a survey of the genus in Brazil based on recent collections and examination of abundant material deposited on Brazilian herbaria we identified seven species: Halimeda cuneata Hering, H. discoidea Decaisne, H. gracilis Harvey ex J. Agardh, H. incrassata (Ellis) Lamouroux, H. opuntia (Linnaeus) Lamouroux, H. simulans Howe and H. tuna (Ellis & Solander) Lamouroux. These species are described in detail, with emphasis on diagnostic characters. Our study has shown that the shape and size of the utricula in surface view, under scanning electron microscopy, can be utilized to discriminate some species. Fertile specimens of Halimeda cuneata and H. discoidea are reported for the first time in the region. Data on vertical and geographical distribution are presented for each species and the southern limit of the genus in the western Atlantic was extended.